(untitled) (Perner’s Contacts, 2015)
It is not possible to envision choice of optimal way of maintenance without rightly functional technical diagnostics which is necessary part of early identification of failure state of machines. It is possible to early identify nascent failures by application of technical diagnostics and thus to plan a suitable time of shutdown of transport mean or machine. This allows preventing of occurrence of shutdowns and thus to reach considerable savings. If the state of machinery is judged on the basis of analysis of applied lubrication, it is a tribotechnical diagnostics (TTD). Results of application of TTD methods are presented in this paper on an example of maintenance management in specific transport company.